Double unilateral, bilateral, and multiple mandibular fractures: an observational study - Moura, Lucas Borin [UNESP]; dos Santos Trento, Guilherme [UNESP]; de Azambuja Carvalho, Pedro Henrique [UNESP]; Granucci, Mariana [UNESP]; de Oliveira, Júlio César Silva [UNESP]; Pereira-Filho, Valfrido Antonio [UNESP] (Springer Nature, 2018)
Purpose: Double and multiple mandibular fractures are associated to high morbidity and functional damage. This study aimed to evaluate the characteristics and outcomes of double unilateral, bilateral, and multiple mandibular fractures. Methods: A 7-year observational retrospective analysis was performed, and the injury-related data were collected from the medical records. Statistical analysis was performed using Fisher’s exact test (p < 0.05). Results: In this period, 283 patients showed mandibular fractures. Of them, 83 (29.7%) had double or multiple mandibular fractures and were included in the study. Double bilateral fractures were more prevalent than multiple or double unilateral. Multiple fractures presented significant association with the combination of load-bearing and load-sharing fixation protocols. Most cases (94.0%) applied at least one type of internal fixation system. However, there was a positive association between condylar fractures and non-surgical treatment (p < 0.01). Moreover, mandibular body fractures were associated with load-bearing fixation (p < 0.01). In 56 cases, no complications were observed (67.5%). Complications were divided into treatment failure (10.8%) and transitory or minor complications (21.7%). There was no statistical association between complications and fracture pattern, fracture-tooth relation, and treatment modality. Conclusion: Double and multiple mandibular fractures represented almost one third of all mandibular fractures, and regardless to treatment protocol, there was no difference about complications. Moreover, although a considerable complication rate was found, most of them were minor or transitory.
Keywords: Complications; Mandibular fractures; Mandibular injuries; Surgical treatment